2023
DOI: 10.1093/geronb/gbad036
|View full text |Cite
|
Sign up to set email alerts
|

Inequities in Mental Health Care Facing Racialized Immigrant Older Adults With Mental Disorders Despite Universal Coverage: A Population-Based Study in Canada

Abstract: Objectives Contemporary immigration scholarship has typically treated immigrants with diverse racial backgrounds as a monolithic population. Knowledge gaps remain in understanding how racial and nativity inequities in mental health care intersect and unfold in midlife and old age. This study aims to examine the joint impact of race, migration, and old age in shaping mental health treatment. Methods Pooled data were obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 90 publications
0
9
0
Order By: Relevance
“…Another school of thought argues that the medical underuse of immigrants, resulting from barriers to accessing health services ( Lin, 2021 ), may be the underlying reason for this “foreign-born health advantage.” As health outcomes and health care access are inextricably intertwined ( Lin, 2022a , b ), the mixed findings on mental health disparities are believed to illuminate, among other factors, underlying health care inequities that lead to the underestimation of mental health conditions among migrant communities ( Lau et al, 2013 ). Mounting evidence from scoping and systematic reviews suggest that compared to the host populations, foreign-born residents seem to underutilize mental health services due to limited health literacy ( Thomson et al, 2015 ), linguistic obstacles ( Wang et al, 2019 ), cultural differences ( Ahmed et al, 2016 ), and discrimination in the host country ( Edge & Newbold, 2013 ).…”
Section: The Healthy Immigrant Paradox and Mental Healthmentioning
confidence: 99%
See 4 more Smart Citations
“…Another school of thought argues that the medical underuse of immigrants, resulting from barriers to accessing health services ( Lin, 2021 ), may be the underlying reason for this “foreign-born health advantage.” As health outcomes and health care access are inextricably intertwined ( Lin, 2022a , b ), the mixed findings on mental health disparities are believed to illuminate, among other factors, underlying health care inequities that lead to the underestimation of mental health conditions among migrant communities ( Lau et al, 2013 ). Mounting evidence from scoping and systematic reviews suggest that compared to the host populations, foreign-born residents seem to underutilize mental health services due to limited health literacy ( Thomson et al, 2015 ), linguistic obstacles ( Wang et al, 2019 ), cultural differences ( Ahmed et al, 2016 ), and discrimination in the host country ( Edge & Newbold, 2013 ).…”
Section: The Healthy Immigrant Paradox and Mental Healthmentioning
confidence: 99%
“…Although a recent study found that undiagnosed depression was higher among female immigrants ( Farid et al, 2020 ), the immigrant health literature tends to homogenize the experience of racialized and White immigrants as a monolithic category ( Brown, 2018 ; Lin & Fang, 2023 ). The intersectionality lens of racialization, migration, and old age has been largely overlooked in mental health epidemiology ( Gkiouleka et al, 2018 ; Lee, 2019 ; Lin, 2023 ). Moreover, racialized immigrants were often compared with their native-born peers of the same ethnic origin (e.g., Alvarez et al, 2019 ), rather than using domestically born Whites as the reference category.…”
Section: Research Gaps and Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations